Experimental study on the single event effects in pulse width modulators by laser testing - 赵雯 郭晓强 陈伟 郭红霞 林东生 王汉宁 罗尹虹 丁李利 王园明 (Journal of semiconductors, 2015)
This paper presents single event effect（SEE） characteristics of UC1845 AJ pulse width modulators（PWMs） by laser testing. In combination with analysis to map PWM circuitry in the microchip dies, the typical SEE response waveforms for laser pulses located in different circuit blocks of UC1845 AJ are obtained and the SEE mechanisms are analyzed. The laser SEE test results show that there are some differences in the SEE mechanisms of different circuit blocks, and phase shifts or changes in the duty cycles of few output pulses are the main SEE behaviors for UC1845 AJ. In addition, a new SEE behavior which manifests as changes in the duty cycles of many output pulses is revealed. This means that an SEE hardened design should be considered.